Intraarticilar and periarticular injections of triamcinolone acetonide and a local anesthetic in knee osteoarthritis (controlled study) - A V Glazunov; E V Zilyaev; A I Zagrebneva; T B Alhimenko (Научно-практическая ревматология)
Efficacy of intraarticular glucocorticoid injections in knee osteoarthritis (OA) is considered to be proved. But authors do not know randomized studies comparing efficacy of intraarticular and periarticular injections of triamcinolone acetonide.Objective. To assess efficacy of intraarticular and periarticular injections of mixture of triamcinolone acetonide (TA) and a local anesthetic (LA) solution in comparison with injections of LA only in pts with knee OA. Material and methods. 86 pts participating in a two-center randomized double blind study ELITA (Efficacy of Local Injection Therapy of osteoArthritis) were included. Each knee joint with pain value higher then 40 mm (on VAS) was randomized for either intraarticular or periarticular injections of novocaine 0,5% 10 ml or its mixture with TA 20 mg. Periarticular injections were performed in regions of ligaments, muscles or tendons insertions. “Pain”, “Activity” and “Functional status” WOMAC scales were assessed at baseline, in 4, 8, and12 weeks after treatment. Results. LA injections were performed in 21 pts (group 1 – control). TA and LA mixture was injected in both knee joints of 8 pts (group 4). Periarticular injections of TA and LA mixture were performed bilaterally in 5 pts (group 6). Group 4 pts had significantly better effect than group 1 pts after 4 (“Pain” and “Functional status” scales) and 8 weeks (“Functional status” scale). Group 6 pts had better results than group 1 pts after 4 (all scales), 8 (“Pain” and “Activity” scales) and 12 weeks (“Activity” scale). In group 6 pts treatment was more effective than in group 4 pts after 4 (all scales), 8 and 12 weeks (“Activity” scale). Conclusion. Efficacy of TA and LA mixture intraarticular and periarticular injections in comparison with isolated LA injections was demonstrated. Effect persisted for at least 8 weeks. Periarticular injections were more effective than intraarticular.